Copper-Catalyzed Photoinduced Radical Domino Cyclization of Ynamides and Cyanamides: A Unified Entry to Rosettacin, Luotonin A, and Deoxyvasicinone - Baguia, Hajar; Deldaele, Christopher; Romero, Eugénie; Michelet, Bastien; Evano, Gwilherm (Synthesis, 2018)
A general and efficient procedure for the copper-catalyzed photoinduced radical domino cyclization of ynamides and cyanamides providing an efficient access to complex tri-, tetra- and pentacyclic nitrogen heterocycles is reported. Upon visible light irradiation in the presence of catalytic amounts of [(DPEphos)(bcp)Cu]PF6 and an amine, a range of unactivated aryl and alkyl iodides were shown to be smoothly transformed to the corresponding radical species, initiating the radical domino cyclization. This procedure provides a unified entry to rosettacin, luotonin A, and deoxyvasicinone that could be efficiently prepared in a limited number of steps.
Keywords: copper catalysis; photocatalysis; radical cyclization; ynamides; cyanamides; rosettacin; luotonin A; deoxyvasicinone